When ECN Lies: Unfairness and Exploitation in L4S Architectures - Correia, Lucas Jaiel de Sousa; Shirmarz, Alireza; Verdi, Fábio Luciano; Maciel Jr., Paulo Ditarso; Almeida, Leandro C. de (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Low Latency, Low Loss and Scalable Throughput (L4S) is a recent architecture proposed by the IETF that enables Internet applications to achieve low queuing latency, low congestion loss, and scalable throughput control. The architecture introduces incremental changes to both hosts and network nodes. On the host side, L4S must incorporate a novel variant of a scalable congestion control capable of recognizing the congestion signals. At network nodes, L4S brings a dual-queue coupled mechanism, in which one queue serves Classic traffic while another serves Scalable traffic, enabling fair bandwidth sharing and harmonious coexistence between TCP flavors. Despite its promise, the architecture faces important security challenges. One of them is the so-called unresponsive Explicit Congestion Notification (ECN) attack, in which a malicious (non-L4S) flow exploits the low-latency queue, causing starvation of compliant traffic. In this work, we conduct an in-depth evaluation of the impact of unresponsive ECN attacks in networks with L4S support. Furthermore, we propose and validate a data-plane-based mitigation mechanism, implemented in P4, capable of identifying and penalizing non-compliant flows, thereby restoring fairness and protecting the low-latency service guarantees of L4S.